Tribological evaluations of modified RBD palm olein-based lubricants in machining processes - T., Norfazillah; Amiril, S. A. S.; Rahim, E. A.; Saiful, A. C. G.; Syahrullail, S. (Malaysian Tribology Society (MYTRIBOS), 2018)
Metalworking fluids from palm oils are desirable as the alternative to mineral oil that possesses negative effects on humans and environment. The aim of this study is to evaluate the tribological and machining performances of the modified refined, bleached and deodorized (RBD) palm olein-based lubricants (MRPOs) containing low number of additives during the tapping torque and orthogonal cutting processes. The additives that were mixed in the neat MRPO were 0.05 wt. % of hexagonal boron nitride (hBN) particles and 1 wt. % of phosphonium-based ionic liquid (PIL). The rheological properties of these MRPOs are also analyzed. Results showed that high synergistic effects of the additives being blended in the MRPOs have exhibited excellent rheological properties and machining performances with high tapping torque efficiency and low cutting force and temperature in comparison with the commercial synthetic ester-based cutting fluid. They prove to have a great potential to substitute the mineral oil-based metalworking fluids in regard to the increasing demands of environment and health concerns for a sustainable manufacturing activity.